PERENCANAAN STRATEGIS SISTEM INFORMASI PADA KELOMPOK PERUSAHAAN DENGAN MENGGUNAKAN METODE WARD & PEPPARD : STUDI KASUS PADA PERUSAHAAN JASA OTOMOTIF - Yunus Fadhillah (Jurnal Informatika dan Bisnis, 2012)
Information technologies that do not support the fulfill business today's needs have to aligned with company strategies and objectives. It is necessary to the strategic planning formulation for information systems that can be implemented within the next five years and if any changes can be customized to the needs. The planning is implementable, modular and integrated in a single platform that works standalone or as a workgroup. Strategic planning framework for information systems is Ward and Peppard (2002) [13], consists input and output stages. Each process uses a clear approach and principles that have been summarized with the characteristics of flexible, modular, deliverables, removing checkpoints, recognize the interactive and cyclic process naturally, the importance of the human side and have the tools and easy diagram. Based on the analysis phases process of strategic planning will result the strategies. That’s IS/IT management strategy proposed to changes in the organizational structure in automotive company service into several parts, manage the operational policies, increase human resources quality and management budged for IS/IT. Business IS strategy transform into future applications portfolio and roadmap for replace all previous existing applications with new applications that have a future impact. IT strategy changes the IT architecture of information systems into applications modules, multi schema databases and in a single integrated data repository. Local network becomes more simple and inter-branch communication to the data repository using a collocation server and the Internet connection. This strategy represents recommendations and guidelines for the management company for the development of infrastructure and information systems from where they had to start and what should be built in accordance with business needs and goals to be achieved by the company in the future.